By setting the two equations equal to each other, we get:
-x^2 + 5x = -x + 5
Simplify this to get:
-x^2 + 5x = -x + 5
Rearranging the equation, we get:
-x^2 + 6x - 5 = 0
Now, we can compare this equation to the table given above to solve for k:
-k^2 + 6k - 5 = 0
By looking at the table, the value of k that makes this equation true is 1.
Therefore, the correct answer is 1.
Use the tables to answer the question. x −x2+5x 0 0 1 4 2 6 3 6 4 4 5 0 x −x+5 −1 6 k 4 3 2 5 0 7 −2 What value of k in the table will be a solution to the equation −x2+5x=−x+5 ?(1 point) Responses
0
4
1
−6
1 answer